Overexpression of Interleukin-23 and Interleukin-17 in the Lesion of Pemphigus Vulgaris: A Preliminary Study. (11th May 2014) - Xue, Jixin; Su, Wenting; Chen, Zhiwei; Ke, Youhui; Du, Xiaojing; Zhou, Qiaochu
Abstract : IL-23/IL-17 axis has been identified as major factor involved in the pathogenesis of several autoimmune diseases; yet its pathogenetic role in pemphigus vulgaris (PV) remains controversial. The aim of this research was to investigate the potential role of IL-23/IL-17 axis in the immunopathogenesis of PV, and correlation between IL-23+ cells and IL-17+ cells was also evaluated. For this purpose, ten patients with PV, three patients with pemphigus foliaceus (PF), and six healthy individuals were allocated to this research. The lesional skin biopsy specimens were obtained before treatment. Then immunofluorescence staining was performed to analyze the expression of IL-23 and IL-17 in the PV/PF patients and the healthy individuals. The results showed that the numbers of IL-23+ and IL-17+ cells were significantly higher in PV lesions, compared to PF lesions and normal control skins, respectively (all P < 0.05 ). Moreover, the correlation between IL-23+ cells and IL-17+ cells was significant (r = 0.7546 ; P < 0.05 ). Taken together, our results provided evidence that the IL-23/IL-17 axis may play a crucial role in the immunopathogenesis of PV and may serve as novel therapeutic target for PV.